2022
DOI: 10.3390/molecules27030797
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into Binding of Huperzine A with Human Serum Albumin: Computational and Spectroscopic Approaches

Abstract: Human serum albumin (HSA) is the most abundant protein in plasma synthesized by the liver and the main modulator of fluid distribution between body compartments. It has an amazing capacity to bind with multiple ligands, offering a store and transporter for various endogenous and exogenous compounds. Huperzine A (HpzA) is a natural sesquiterpene alkaloid found in Huperzia serrata and used in various neurological conditions, including Alzheimer’s disease (AD). This study elucidated the binding of HpzA with HSA u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 45 publications
(54 reference statements)
0
13
0
Order By: Relevance
“…HupA showed excellent binding affinity to Tf with a binding constant of 0.2 × 10 6 M –1 and is comparable to the binding constant obtained for binding of HupA with HSA. 28 Hence, the in silico observations coupled with the fluorescence binding affirm significant binding of HupA to Tf.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…HupA showed excellent binding affinity to Tf with a binding constant of 0.2 × 10 6 M –1 and is comparable to the binding constant obtained for binding of HupA with HSA. 28 Hence, the in silico observations coupled with the fluorescence binding affirm significant binding of HupA to Tf.…”
Section: Resultsmentioning
confidence: 70%
“…Hup A has shown inhibitor effects against the tetrameric form of ACh, which is present in abundance, and other drugs such as rivastigmine inhibit the scarce monomeric form . A recent study reported binding of HupA with the most abundant plasma protein, human serum albumin (HSA) . Thus, in lieu of the importance of Tf in AD therapeutics and the potential of HupA as an excellent therapeutic candidate for AD, this study was performed to decipher the binding mechanism of HupA with Tf.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a bid to maintain the structural conformation of the protein, hydrogen bonds play a pivotal role [ 18 ]. The analysis of hydrogen bonding aids in assessment of the stability of the protein and protein–ligand complexes [ 19 ]. Thus, herein, we analysed the intramolecular hydrogen bonding to decipher the stability of the MARK4 and MARK4–Mtf complex ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
“…The two well-known binding sites available on HSA are Sudlow site I and II, located in subdomain IIA and IIIA [ 17 ]. A pivotal step in the domain of drug discovery is the investigation of the pharmacokinetics and pharmacodynamics of drugs [ 18 ]. The abundance of HSA makes it an important factor in the pharmacokinetic behavior of many drugs as it affects their efficacy and delivery rate, and the binding of a drug to HSA is a critical factor determining its pharmacological profiling and distribution [ 19 ].…”
Section: Introductionmentioning
confidence: 99%